Assessment of the accuracy of dried blood spot (DBS) sample in HIV-1 viral load as compared to plasma sample using Abbot assay - Benedicto, Prisca; Dladla, Philan; Goba, Gloria; Shawa, Isaac Thom (International Journal of Research in Medical Sciences, 2017)
Background: HIV has claimed millions of lives with the Sub-Saharan Africa being the most affected. There is a significant increase in access to antiretroviral drugs which also demands frequent monitoring to determine the drug effectiveness and efficacy. Thus there is a great need to evaluate simplified methods to monitor treatment with such antiretroviral drugs. Use of dried blood spots (DBS) can be ideal if evaluated in resource limited countries such as Malawi since they are easy to collect, store and convenient. The main objective of this study was to evaluate the accuracy of a dry blood spot sample in the quantification of viral particles in HIV reactive patients using the Abbott m2000rt assay. Methods: 87 participants were recruited from the ART clinic at Queen Elizabeth Central Hospital using convenience sampling method. 29 were on antiretroviral therapy and 58 had not started the therapy. HIV-1 RNA extraction and quantification was performed from DBS and plasma using Abbott m2000sp and m2000rt systems respectively. The results were statistically analyzed by Bland-Altman method using medcalc software version 12.6.1. Results: 66 paired samples with detectable viral loads were analysed. These gave a correlation of 0.98. The mean difference was 0.05 log10 copies/ml with a standard deviation of 0.17 at 95% confidence interval.The Bland-Altman plots showed limits of agreement which ranged from -0.38 to 0.28 log10 copies/ml at 95% confidence interval. Conclusion: Results showed strong agreement between the plasma and DBS samples. A slight and clinically insignificant difference was observed between the two methods. A larger sample size can give support to the study findings. Since samples were less than a week old, it is not known if the results would be different if they were to be stored for a longer period.